Large scale segmental bone defect healing through the combined delivery of VEGF and BMP‐2 from biofunctionalized cortical allografts. Issue 4 (8th October 2018) - Sharmin, Farzana; O'Sullivan, Michael; Malinowski, Seth; Lieberman, Jay R.; Khan, Yusuf
Abstract: Large scale cortical allografts suffer from poor incorporation and healing and often end in graft failure 5–10 years after implantation. To reduce these failures we have developed a growth‐factor loaded cortical allograft capable of delivering one or two factors with a degree of temporal control and precision that permits the early release of one growth factor followed by the later and more sustained release of the other. We have loaded vascular endothelial growth factor (VEGF) and bone morphogenetic protein‐2 (BMP‐2), both critical components of bone formation and repair, onto cortical long bone allografts such that the VEGF is released first and followed shortly by BMP‐2. Coated and factor‐loaded allografts were placed into a critical sized rat femoral segmental defect and allowed to heal for either 4 or 8 weeks. Healing at each time point was compared to allografts loaded with only BMP‐2 and allografts containing no growth factors. Results indicate statistically significant increases in new bone formation from 4 to 8 weeks around allografts loaded with both VEGF and BMP‐2 over allografts with no growth factor, suggesting that factor‐loaded polymer‐coated allografts delivering multiple factors with temporal precision may provide a new off‐the‐shelf tool to the orthopedic surgeon for management of large‐scale orthopedic bone defects. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1002–1010, 2019.